The nature and value of vagueness in the law - Asgeirsson, Hrafn (London [England] : Hart Publishing, 2020)
c
1. Authority, Communication and Legal Content -- 2. On the Instrumental Value of Vagueness in the Law -- 3. Vagueness and Power Delegation in Law -- 4. Vagueness, Uncertainty and Behaviour -- 5. On the Possibility of Non-literal Legislative Speech -- 6. Textualism, Content and Interpretation -- 7. Resolving Cases of Vagueness -- 8. Legal Practice and Theories of Vagueness.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Law -- Interpretation and construction; Law -- Philosophy; Vagueness (Philosophy); Jurisprudence & philosophy of law; Electronic books